Rabbit semen fertility after heterospermic insemination with spermatozoa of different capacitation time - YPSILANTIS (Π. ΥΨΗΛΑΝΤΗΣ) P.; SARATSIS (Φ. ΣΑΡΑΤΣΗΣ) Ph.; SAMOUILIDIS (Σ. ΣΑΜΟΥΗΛΙΔΗΣ) S. (Journal of the Hellenic Veterinary Medical Society, 2018)
The influence of mixing heterogeneous sperm populations in rabbit semen fertility was studied. Eighty female rabbits which were divided in 4 groups (1,2,3 and 4) in = 20.) and 3 males of proven fertility were employed. The animals of group 1,2 and 3 were inseminated with semen from male A j, A2 and A3, respectively, while those of group 4 were inseminated with a mixture containing equal number of progressively motile spermatozoa from each of the above mentioned males ( A 1 + 2 + 3 ) (heterospermic insemination). Animals of each group were divided into 4 subgroups according to the insemination time (15,10, 5 and 0 hours prior the expected ovulation). In each group, differences were observed (P<0.05) between subgroups at the percentage of animals that delivered, indicating differences between males at the time and the duration of sperm capacitation in vivo. Based on the percentage of the animals that delivered and the litter size, semen fertility was improved after the application of heterospermic insemination, at all insemination times. This improvement was attributed to the extension of the time during which capacitated spermatozoa were present in the female genital tract due to the mixture of heterogeneous sperm populations of different capacitation time.